Evidence that the loss of colonic anti-microbial peptides may promote dysbiotic Gram-negative inflammaging-associated bacteria in aging mice - Forsyth, Christopher B.; Shaikh, Maliha; Engen, Phillip A.; Preuss, Fabian; Naqib, Ankur; Palmen, Breanna A.; Green, Stefan J.; Zhang, Lijuan; Bogin, Zlata R.; Lawrence, Kristi; Sharma, Deepak; Swanson, Garth R.; et al. (Frontiers in Aging, 2024)
Introduction: Aging studies in humans and mice have played a key role in understanding the intestinal microbiome and an increased abundance of “inflammaging” Gram-negative (Gn) bacteria. The mechanisms underlying this inflammatory profile in the aging microbiome are unknown. We tested the hypothesis that an aging-related decrease in colonic crypt epithelial cell anti-microbial peptide (AMP) gene expression could promote colonic microbiome inflammatory Gn dysbiosis and inflammaging. Methods: As a model of aging, C57BL/6J mice fecal (colonic) microbiota (16S) and isolated colonic crypt epithelial cell gene expression (RNA-seq) were assessed at 2 months (mth) (human: 18 years old; yo), 15 mth (human: 50 yo), and 25 mth (human: 84 yo). Informatics examined aging-related microbial compositions, differential colonic crypt epithelial cell gene expressions, and correlations between colonic bacteria and colonic crypt epithelial cell gene expressions. Results: Fecal microbiota exhibited significantly increased relative abundances of pro-inflammatory Gn bacteria with aging. Colonic crypt epithelial cell gene expression analysis showed significant age-related downregulation of key AMP genes that repress the growth of Gn bacteria. The aging-related decrease in AMP gene expressions is significantly correlated with an increased abundance in Gn bacteria (dysbiosis), loss of colonic barrier gene expression, and senescence- and inflammation-related gene expression. Conclusion: This study supports the proposed model that aging-related loss of colonic crypt epithelial cell AMP gene expression promotes increased relative abundances of Gn inflammaging-associated bacteria and gene expression markers of colonic inflammaging. These data may support new targets for aging-related therapies based on intestinal genes and microbiomes.